POSS-based starlike hybrid helical poly(phenyl isocyanide)s: their synthesis, self-assembly, and enantioselective crystallization ability. Issue 27 (29th June 2021) - Zou, Hui; Li, Qian-Wei; Wu, Qi-Liang; Liang, Wen-Quan; Hou, Xiao-Hua; Zhou, Li; Liu, Na; Wu, Zong-Quan
Abstract : Well-defined starlike hybrid helical poly(phenyl isocyanide)s with POSS cores were designed and synthesized, and their self-assembly behaviour and enantioselective crystallization ability were investigated. Abstract : Polyhedral oligomeric silsesquioxane (POSS) based starlike hybrid helical poly(phenyl isocyanide)s (PPIs) with well-defined structures were designed and prepared in this contribution. The POSS modified with Pd(ii ) complexes (POSS-Pd(ii )) was firstly obtained. Then well-defined starlike hybrid helical PPIs with POSS cores were synthesized through the polymerization of phenyl isocyanide monomers using POSS-Pd(ii ) as the initiator. The polymerization proceeded in a living and controlled manner. Meanwhile, polymerization of chiral phenyl isocyanides with decyl chain modified pendant l - or d -alanine afforded optically active hybrid starlike helical PPIs with preferred handedness. What's more, amphiphilic starlike hybrid helical PPI block copolymers showing thermoresponses were easily obtained, and their self-assembly and thermo-responsive behaviours were studied. In addition, cross-linked hybrid helical PPIs were obtained via the transesterification reaction between pentafluorophenyl ester and cystamine. Benefitting from the essential chirality of the handed helical PPIs, the cross-linked hybrid PPIs showed excellent ability in the enantioselective crystallization of racemic compounds. The enantiomeric excess (ee) of the induced crystal of threonine could be up to 95%.